DIGENIC TREMATODE INFECTION IN THE EDIBLE OYSTER CRASSOSTREA MADRASENSIS (PRESTON) - Samuel, D (Indian Journal of Fisheries, 2011)
Our knowledge of the trematode parasites on marine animals of Indian waters is limited. Recently, Silas (1962) reviewed the trematodes parasitic on scomberoid fishes, but, as yet, nothing is known about parasitic larval trematodes in the edible oyster. Mass mortality of oysters due to parasitic cercaria is reported from several other places. Howell (1967) observed that the decline in abundanc of oysters in New Zealand beds was largely due to epidemical outbreak of Bucephalus longicornutus.